COVID-19 Exceptionalism: Explaining South Korean Responses. Issue 1 (2nd January 2022) - Chekar, Choon Key; Kim, Hyomin
Abstract: COVID-19 has presented challenges across the globe that led to a number of shared lessons to be learnt. Yet, we are inundated with comparative accounts that characterize national pandemic responses as inherent and unique to certain nation states, which, we argue, led to COVID-exceptionalism. This article challenges "cultural" explanations of South Korea's "successful" responses to COVID-19 crisis. The popular narrative has been that Korea's cluster-based mitigation strategy was sustained by rigorous contact tracing and mass testing systems, and this was made possible by three distinctive elements of pandemic preparedness: 1) Korean "culture" of normalizing face-covering, 2) Korean citizens' consensus of prioritizing public health to privacy, and 3) Korea's IT infrastructure enabling efficient digital contact tracing. By debunking the three myths, we demonstrate why neither the Asian "authoritarian advantages" thesis nor the counter-argument of "Asian civility" adequately captures the reality of Korea's reaction to the COVID pandemic. The ways in which risks are conceptualized as manageable objects produce particular modes of allocating responsibilities for risk mitigation, when dealing with a relatively unknown virus. COVID-exceptionalism may cause not only the issue of reinforcing "(East) Asian"/"Western" stereotypes, but also other problems such as implicitly granting political impunity to those responsible for coordinating COVID-19 responses.